Ascending Tonic Clonic Seizure Syndrome after Percutaneous Vertebroplasty - Guido Zarattini; Adam Farrier; Federico Sibona (Case Reports in Orthopedics)
Background Context. Cement leakage is not a rare complication of vertebroplasty, but ascending tonic clonic seizure syndrome is exceptionally rare. We herein report the first case to our knowledge of this complication related to vertebroplasty. Purpose. We herein report the first case of ascending tonic clonic seizure syndrome following epidural cement leakage after percutaneous vertebroplasty in a patient with multiple osteoporotic compression fractures. Study Design. Case report. Methods. A 64-year-old woman with T8, T10, L2, and L4 osteoporotic compression fractures underwent percutaneous vertebroplasty using polymethylmethacrylate. 40 minutes after the procedure the patient started suffering back and leg pain, having repetitive myoclonic jerks lasting 15 seconds of the lower extremities, spasm of the back, dyspnea, sinus tachycardia, hypoxemia, and metabolic acidosis. Results. The patient recovered completely due to a combination of early effective resuscitation and considered definitive management. Conclusions. Percutaneous vertebroplasty with polymethylmethacrylate is relatively safe but has few dangerous complications, which should be prevented by a meticulous technique and excellent image quality.